Evaluation of Insulin Use and Hypoglycemia in Hospitalized Elderly Patients. Issue 11 (December 2017) - Bach, Quyen N.; Gilmore, Rod A.; Sheffield, Melody C.; Hawkins, W. Anthony
Background: Routine administration of correctional insulin is no longer recommended as a primary strategy to treat hyperglycemia in hospitalized patients. Studies have demonstrated significant improvement in glycemic control in patients treated with basal and correctional insulin (B+C) versus correctional insulin alone (C). However, the effect of C or B+C on hypoglycemic events is not well understood.Objective : The objective of this study was to investigate the effect of B+C versus C on hypoglycemic events in hospitalized elderly patients.Methods : A single-center retrospective review of patients at least 65 years old that were admitted between April and July 2016, who were prescribed any type of insulin. Exclusion criteria included admission to the intensive care unit (ICU) on hospital admission, history of hypersensitivity to insulin, or insulin use for the management of hyperkalemia. Patients were divided based on the insulin regimen prescribed, B+C or C. The primary outcome of the study was the incidence of hypoglycemic episodes between groups. Secondary outcomes included severity of hypoglycemia, hospital length of stay (LOS), hospital mortality, and ICU transfer. Hypoglycemia was defined as a blood glucose level less than 70 mg/dL.Results: A total of 709 patients were included, with 144 (20.3%) prescribed B+C and 565 (79.7%) prescribed C. Incidence of hypoglycemia was greater in the B+C group than C (29.1% vs 12.6%, p=0.012 ). The average blood glucose readings during hypoglycemic episodes between B+C and C were 50 mg/dL and 52.5 mg/dL, respectively ( p<0.01 ). There was no difference observed in hospital LOS. No patients required ICU admission within 24 hours of a hypoglycemic event or died during the index hospitalization.Conclusion: There is a higher incidence of hypoglycemia in elderly patients prescribed basal plus correctional insulin than correctional insulin alone.